Factors contributing to mother-Daughter talk about sexual health education in an Iranian urban adolescent population - Maryam Torki Harchegani; Maryam Dastoorpoor; Mojgan Javadnoori; KHadijeh SHiralinia (Wolters Kluwer Medknow Publications, 2021)
Background: Parent-adolescent dialog on sexual issues reduces high-risk sexual behavior in adolescents. However, many adolescents are deprived of such training. Several factors may affect the sexual dialog between parents and adolescents. This study aimed to investigate the factors associated with mother-adolescent daughter dialog on sexual health matters in Iran. Materials and Methods: This cross-sectional study was carried out on 363 female adolescents aged 14-18 years in Ahvaz-Iran, between June 2015 and January 2016. Data collection was conducted utilizing multi-stage cluster sampling in high schools using the Parent-adolescent sexual dialog questionnaire and the parent-adolescent general dialogue questionnaire. The validity of the questionnaires was confirmed using content and face validity and their reliability was confirmed through internal consistency. The data were analyzed using descriptive statistics, Pearson's correlation coefficient, independent one-sample and two-sample t-tests, one-way ANOVA, and Post-HOC (Duncan) test. Results: The mean score of mother-daughter sexual dialog had a significant relationship with mother's education (F = 4.03, p > 0.003), adolescent's major (F = 4.48, p < 0.004), mother-daughter general communication (p < 0.001), and emotional relationship with parents (F = 6.47, p < 0.002). The more is the mother-daughter general communication, the more will be their sexual communication (p < 0.001). There was no relationship between the score of mother-daughter sexual communication and the age of mother or adolescent, parents' job, parents' marital status, and having sisters (p = 0.86). Conclusions: Some demographic characteristics of parents and adolescents, and the parent-adolescent emotional relationship can affect the communication between them about sexual issues. So efforts to enhance this communication should consider these factors as mediator variables.